Feminism and methodology : social science issues - Harding, Sandra G. (Indiana University Press, 1987)
"Appearing in the feminist social science literature from its beginnings are a series of questions about methodology. In this collection, Sandra Harding interrogates some of the classic essays from the last fifteen years in order to explore the basic and troubling questions about science and social experience, gender, and politics."--Book cover